Ionospheric photoelectrons at Venus: Case studies and first observation in the tail. (August 2015) - Tsang, S.M.E.; Coates, A.J.; Jones, G.H.; Frahm, R.A.; Winningham, J.D.; Barabash, S.; Lundin, R.; Fedorov, A.
Abstract: The presence of photoelectrons in ionospheres, including that of unmagnetised Venus, can be inferred from their characteristic spectral peaks in the electron energy spectrum. The electrons within the peaks are created by the photoionisation of neutrals in the upper atmosphere by the solar HeII 30.4 nm line. Here, we present some case studies of photoelectron spectra observed by the ASPERA-4 instrument aboard Venus Express with corresponding ion data. In the first case study, we observe photoelectron peaks in the sunlit ionosphere, indicating relatively local production. In the second case study, we observe broadened peaks in the sunlit ionosphere near the terminator, which indicate scattering processes between a more remote production region and the observation point. In the third case study, we present the first observation of ionospheric photoelectrons in the induced magnetotail of Venus, which we suggest is due to the spacecraft being located at that time on a magnetic field line connected to the dayside ionosphere at lower altitudes. Simultaneously, low energy ions are observed moving away from Venus. In common with observations at Mars and at Titan, these imply a possible role for the relatively energetic electrons in producing an ambipolar electric field which enhances ion escape. Highlights: First observations of ionospheric photoelectron peaks in the tail of Venus. At times the peaks are broadened, implying scattering. Indicates a magnetic connection between the observation point and the dayside ionosphere. Simultaneous ion observations support idea of an ambipolar electric field.